Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Audit Delay Di BEI Tahun 2019-2021 - Hastuti Olivia; Tri Dessy Fadillah; Astrid Aulia Farizki; Annisa Namira; Heprina Hera Rezeki (ARBITRASE: Journal of Economics and Accounting, 2022)
Financial reports are reported at the end of each accounting period. Regulations for companies registered with Busfa Securities Indonesia must provide audited financial statements no later than four months after the end of the book closing. Audit delay affects companies listed on the Indonesian Stock Exchange. The purpose of this study is to see how much influence the company has on audit delay. This study uses quantitative methods with Eviews 10 software and uses panel data. The results of this research show that profitability influences audit delay, company size influences audit delay, and profitability, company size influences audit delay simultaneously. It is hoped that companies listed on the Indonesia Stock Exchange will not be late in submitting their financial reports, because potential investors will be able to see the mistakes made by the company.